ASSESSMENT OF TIME OF THE BREAK IN FUNCTIONING OF THE ATC RADIO AIDS CHANNEL - V. E. Emelyanov; V. A. Ivanenko (Научный вестник МГТУ ГА, 2016)
The authors provide a model that allows estimating the time of the break of functioning navigation and ATC that make up the information channel.